Characterization, stability assessment, antioxidant evaluation and cell proliferation activity of virgin coconut oil-based nanostructured lipid carrier loaded with Ficus deltoidea extract - Azmi, Nor Azrini Nadiha; Hasham, Rosnani; Ariffin, Farah Diana; Elgharbawy, Amal A.M.; Mohd. Salleh, Hamzah (MDPI, 2020)
In this study, the Ficus deltoidea extract loaded nanostructured lipid carrier was prepared by using the melt emulsification homogenization method. Virgin coconut oil is used as liquid lipid, while glyceryl monostearate is the solid lipid. Particle size, zeta potential, entrapment efficiency, drug loading and morphology of the obtained nanostructured lipid carrier (NLC) were measured. The size of the nanostructured lipid carrier incorporated with Ficus deltoidea (FDNLC) is 158.0 ± 1.3 nm, with a polydispersity index of 0.15 ± 0.02. The zeta potential obtained is −42.3 ± 1.5 mV. The encapsulation efficiency and active ingredient loading capacity for FDNLC is 87.4% ± 1.3% and 8.5% ± 1.2%, respectively. The shape of FDNLC is almost spherical and the stability assessment showed that the obtained formulation is at least stable for 40 days. When compared with the positive controls, which are Trolox and ascorbic acid, FDNLC shows the highest antioxidant value. Cell proliferation activity study indicates that FDNLC is not toxic to cells, and FDNLC could potentially treat damage by ultraviolet B (UVB) irradiation.